EFFECTIVENESS OF FAMILY THERAPY APPROACH TO REDUCE SIBLING RIVALRY IN CHILDREN AGED 8-10 YEARS IN KABAT VILLAGE, BANYUWANGI : EFEKTIVITAS PENDEKATAN FAMILY THERAPY UNTUK MENGURANGI SIBLING RIVALRY PADA ANAK USIA 8-10 TAHUN DI DESA KABAT BANYUWANGI - Erma putri dwi ambarsari; Heriberthus Wicaksono; Ratna Wulandari (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
The study was conducted to determine the effectiveness of the family therapy approach to reduce sibling rivalry in children aged 8-10 years in Kabat Village, Banyuwangi. This study used a quasi-experiment with a pre-test and post-test group design. This study uses purposive sampling techniques to determine the sample, the sample taken consists of 5 families who have 2 children aged 8-10 years with a close age gap who experience high sibling rivalry problems. The data collection techniques used were sibling rivalry questionnaires, observations, and interviews. The researcher used a data analysis technique with a statistical program for social sciences (SPSS) version 21 test. The results of the study show that "Group Counseling with the Family Therapy approach is effective in overcoming sibling rivalry in children aged 8-10 years in Kabat village Banyuwangi” shows that the average sibling rivalry questionnaire score on the pre-test is 373 and the average sibling rivalry questionnaire score on the post-test is 277. This shows that there has been a decrease in the average sibling rivalry questionnaire results. The results of SPSS version 21 the produces value analysis data calculations are 27.49 > 2.132, so because H0 is rejected, Ha is accepted which reads “The Application of Family Therapy Has Proven Effective in Reducing Sibling Rivalry in Children aged 8-10 Years in The Village of Kabat Banyuwangi”.